ANALISIS FAKTOR - FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENDAPATAN PETANI KENTANG DI DESA SEMANGAT KABUPATEN KARO - TONNY HENDRA NADEAK (LP2MTBM MAKARIOZ, 2022)
The research was conducted in The Spirit Village of Merdeka Subdistrict, Karo Regency, North Sumatra Province. This studyaims to find out the influence of socioeconomic factors on the level of net income of potato farmers in the research area. Thearea is the center of potato production in Karo Regency. The number of samples is 38 KK. The results showed thatsimultaneously the level of education (X1), land area (X2), age (X3) and education level (X4) significantly affect the incomeof potato farmers (Y) where F-calculated values of 98.68 > F-table (2.41). Partially the variables of education level (X1) andfarming experience (X5) have a positive and significant effect on potato farming income, while land area (X2) and age (X3)have a positive effect but do not have a significant effect on potato farming income.